Relationship between E23K (an established type II diabetes-susceptibility variant within KCNJ11), polycystic ovary syndrome and androgen levels. - Barber, T; Bennett, A; Gloyn, A; Groves, C; Sovio, U; Ruokonen, A; Martikainen, H; Pouta, A; Taponen, S; Weedon, M; Hartikainen, A; Wass, J; et al. (2007)
Polycystic ovary syndrome (PCOS) is strongly associated with hyperinsulinaemia and type II diabetes (T2D). Sequence variation within KCNJ11 (encoding Kir6.2, the beta-cell inwardly rectifying potassium channel) is implicated in the pathogenesis of neonatal diabetes, hyperinsulinaemia of infancy and multifactorial T2D. Comprehensive tagging studies have demonstrated that the KCNJ11 E23K variant (or ABCC8 A1369S in LD>0.9) is responsible for the known association between KCNJ11 and T2D. Given the phenotypic overlap between PCOS and T2D, we investigated whether E23K is involved in susceptibility to PCOS and related traits. Case-control analyses for the KCNJ11 E23K variant were performed in (a) 374 PCOS cases and 2574 controls of UK British/Irish origin, and (b) 550 women with PCOS symptoms and 1114 controls from a Finnish birth cohort. The relationship between E23K genotype and androgen levels (a key intermediate phenotype relevant to PCOS) in 1380 samples was studied. The UK case-control analysis revealed no association between E23K genotypes and PCOS status (P=0.49; Cochran-Armitage test), and no significant relationship between E23K genotype and androgen measures in the samples for which these phenotypes were available (P=0.19). Similarly, the Finnish case-control analysis showed no association between E23K genotypes and PCOS status (P=0.75; Cochran-Armitage test), and no significant relationship between E23K genotype and androgen measures in the samples for which these phenotypes were available (Finnish controls, P=0.25; Finnish cases, P=0.08). In conclusion, these data (involving >4600 subjects) provide no evidence that common variants of the KCNJ11 E23K polymorphism have a major influence on PCOS susceptibility, though modest effect sizes (OR<1.25) cannot be excluded.